(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
Permian brachiopods from Oman are well-known as valuable tools for correlation and palaeobiogeographical and palaeoclimatic reconstructions. Here, we describe a new brachiopod fauna from the Qarari Unit of the allochthonous Batain Group in northeast Oman. Brachiopods were collected from four localities: Wadi Khawr al Jaramah (WKJ), Jebel Qarari (JQ1), Jebel X (JX3) and Shiya (SH11). The age of the fossiliferous localities is wellconstrained to the late Kungurian-early Roadian by conodonts and fusulines, in agreement with the age suggested by the brachiopod ranges. The brachiopod fauna consists of 339 specimens belonging to 68 species of 8 orders, among which five species are here identified as new. Based on the taphonomic attributes and the analysis of the brachiopod life-styles, the assemblages from the Qarari Unit are interpreted as life assemblages thriving on varied substrates, with limited post-mortem exposure on the sea floor and rapid burial at depths around the storm wave base. Based on the generally high biodiversity indices (Shannon-Wiener and Margalef indices), the Qarari brachiopod fauna can be considered a biodiversity hotspot, only comparable, in term of biodiversity, to the coeval faunas from West Texas and South China. However, palaeobiogeographical affinities of the Qarari brachiopods with these faunas are scanty, as well as the affinities with coeval faunas from the northern Gondwana margin and the Cimmerian and Cathaysian blocks, except for some similarities with the upper Kungurian brachiopods of Myanmar. This may be explained by the fact that the Qarari succession was deposited in the Madagascan arm of Neo-Tethys, and thus rather isolated from the main Gondwanan margin.